Perception of bioethical principles applied in hydrotherapeutic practices: echoes of therapists - Marcone-Dapelo, Pamela (Acta Bioethica, 2024)
Article reports an investigation into the application of the bioethical principles of personalism in hydrotherapeutic practice internationally. A qualitative, phenomenological, purposive and opinionated sampling methodology was used. The sample consisted of 12 international senior aquatic therapists, who participated in semi-structured online interviews. Thematic categorical content analysis was carried out with the support of Atlas Ti software, version 9. As a result, four principles of personalism and three emerging categories were identified: values, principle of vulnerability and the cost-benefit principle. It is concluded that hydrotherapeutic practice is consistent with the personalist current. A principle of utilitarianism and the Barcelona Declaration emerges, as well as values such as honesty, respect and humility. The need to deepen the bioethical principles of personalism in general aquatic practice, as well as in the training processes and bioethical competences acquired by therapists, is raised.